Penerapan Nilai-Nilai Murni Menerusi Komsas Dalam Sistem Pendidikan Malaysia - Chew Fong Peng (HISKI, 2009)
Literature Component (KOMSAS) in Bahasa Melayu in Malaysia stresses on the fertilizing and comprehending of the pure values of the Malaysian society which are based on religion, tradition and customs, and in accordance with the universal moral values. This paper will only discuss 16 pure values in three dramatic scripts in the anthology Anak Laut, Level IV. Serunai Malam by Usman Awang. Titik-titik Perjuangan by Kala Dewata and Seri Nara by Shahrom Husain have the same theme, i.e. the spirit of patriotism, love of the country and nation in the people's heart. A study was done to 60 students of Level IV specializing in science, with a considerable balance of ethnicities, gender and social-economic status (SES). The result of the study showed that male Malay students from higher social class got a higher min score than non-Malay female students from middle class or lower class. Among the three factors SES has the strongest influence in the students' attitude toward the pure values contained in the three analyzed dramas. Considering this, the pure values contained in literary works should be used widely in the national education system to build tolerance and to draw those values near to different ethnic groups.